2015
DOI: 10.1515/ppb-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Polish version of the Trait Emotional Intelligence Questionnaire-Short Form

Abstract: The study was aimed at validating the Polish version of the Trait Emotional Intelligence Questionnaire-Short Form (TEIQue-SF). Our findings confirm the reliability and validity of the scale. With respect to reliability, internal consistency coefficients of the TEIQue-SF were comparable to those obtained using the original English version. The evidence of the validity of the TEIQue-SF came from the pattern of relations with the other self-report measure of EI, personality measures, as well as affective and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
(54 reference statements)
2
18
0
1
Order By: Relevance
“…It also extends previous research which demonstrated that trait EI was positively related to self-reported social competences (Szczygieł et al, 2015). In the current study we were able to rule out the disadvantages associated with self-reported social competence, such as self-deception (a positively biased response that respondents actually believe to be true) and impression management (an intention to create a favourable impression and deceive others) (Paulhus, 1984).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…It also extends previous research which demonstrated that trait EI was positively related to self-reported social competences (Szczygieł et al, 2015). In the current study we were able to rule out the disadvantages associated with self-reported social competence, such as self-deception (a positively biased response that respondents actually believe to be true) and impression management (an intention to create a favourable impression and deceive others) (Paulhus, 1984).…”
Section: Discussionsupporting
confidence: 87%
“…Correlations between trait EI and openness, agreeableness, and conscientiousness are also significant (and positive), but rather modest in size (Mikolajczak et al, 2007;Szczygieł et al, 2015;Wytykowska & Petrides, 2007). Furthermore, personality traits have also been linked to peer assessment.…”
Section: Objectives Of Researchmentioning
confidence: 98%
See 3 more Smart Citations